دراسة تكتونو- زلزالية وبترولوجية لمنطقة الانهدام السوري (Latakia University Journal -Basic Sciences Series, 2018)
تشير المعطيات الزلزالية إلى  حركة تتراوح  قيمتها من2,7 إلى 3,3 مم/ سنة، ومعامل تسارع زلزالي ضعيف تتراوح قيمته بين 0 – 0,25 سم /مربع السطح، وزلزالية حديثة موثقة لا يزيد كبرها(قدرها) عن 6 درجات على مقياس ريختر،مما يجعل من  سورية  نطاقاً ضعيفاً إلى معتدل الشدّة الزلزالية. تترافق هذه الزلزالية مع بركنة امتدت منذ الميزوزوي حتى الوقت الحالي على امتداد الانهدام السوري. وهي بركنة قلوية كلسية، حملت معها إلى السطح حشوات معطفية مكونة من بيريدوتيت وبيروكسنيت تضمّ مختلف الأنواع البتروغرافية، التي تشير خصائصها البتروجيوكيميائية إلى أنّها توازنت في سحنة الليرزوليت ذوغرينا قبل أن تبدأ الصعود مروراً بسحنة الليرزوليت ذوسبينل. إنّ وجود فلز السافرين بشكل محلول صلب في الكلينوبيروكسين يدعم ميكانيكية الصعود هذه المرتبطة بعملية الاستعاضة المعطفية. يشير تطور كبر الهزات الأرضية إلى أنّها تناقصت منذ القديم إلى وقتنا الحالي بشكل موازٍ لانتقالها من سحنة الليزروليت ذوغرينا إلى سحنة الليرزوليت ذوسبينل، وعليه فإنّ شدة  النشاط الزلزالي  قد تراجعت من الماضي إلى وقتنا الحالي. Seismic data indicates a rate movement estimated at 2,7-3,3 mm/y, seismic acceleration coefficient estimated at 0-0,25 cm/S2, and a recent seismicity record with a  magnitude  not exceeding 6 on the Richter scale. This indicates that Syria represents a low to moderate seismic zone. This seismicity is associated with a volcanism dating since the Mesozoic to the present time along the Syrian rift. It is a calco-alcalin composition, which has broght up to the surface a quantity of mantelic xenoliths. They are originated in the  garnet lherzolite  stability field before passing to the spinelle lherzolite field. The presence of saphirine in exsolution in clinopyroxen supports this mechanism  related to the metasomatic process .  Earthquakes magnitude evolution indicates that it was higher in the past, at the level of the garnet lherzolite, and becomes less in the spinelle lherzolite level. Thus the seismicity decreases from the past to the present.